Media ownership : the economics and politics of convergence and concentration in the UK and European media - Doyle, Gillian (SAGE, 2002)
This book offers an up-to-date and timely critical overview of the contemporary media environment. The author: - examines the socio-political and cultural implications of media concentration - analyses how policy makers have responded - investigates the commercial and strategic advantages of consolidation - assesses the relationship between media ownership and economic performance, and - looks at the balance of power between politicians and media owners.